Why Join a Team? - David J. Cooper; Krista Saral; Marie Claire Villeval (Institute of Labor Economics (IZA), 2019)
We present experiments exploring why high ability workers join teams with less able co-workers when there are no short-term financial benefits. We distinguish between two explanations: pro-social preferences and expected long-term financial gains from teaching future teammates. Participants perform a real-effort task and decide whether to work independently or join a two-person team. Treatments vary the payment scheme (piece rate or revenue sharing), whether teammates can communicate, and the role of teaching. High ability workers are more willing to join teams in the absence of revenue sharing and less willing to join teams when they cannot communicate. When communication is possible, the choice of high ability workers to join teams is driven by expected future financial gains from teaching rather than some variety of pro-social preferences. This result has important implications for the role of adverse selection in determining the productivity of teams.
Keywords: C92; D23; M52; M53; J24; 330; teams; teaching; revenue sharing; social preferences; self-selection; experiment